2013
DOI: 10.1039/c3tc30257a
|View full text |Cite
|
Sign up to set email alerts
|

Self-stratified semiconductor/dielectric polymer blends: vertical phase separation for facile fabrication of organic transistors

Abstract: Semiconducting/insulating polymer blends are promising materials for use in organic thin film transistor (OTFT) applications. Here, vertically phase-separated poly(3-hexylthiophene) (P3HT)-top and poly(methyl methacrylate) (PMMA)-bottom blend films were developed for the facile fabrication of OTFTs with excellent electrical properties. The microstructures of the blend films could be adjusted simply by altering the film processing conditions, which impacted the electrical properties of the OTFTs based on the bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
69
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(73 citation statements)
references
References 55 publications
4
69
0
Order By: Relevance
“…The increased time resulted in diF-TES-ADT crystals with larger grain size. This is in accordance with the work of Qiu et al, which reports similar concentration effects in P3HT/PMMA blends [9]. When the solution concentration was increased further (30 mg/ml), spherulites with a Maltese cross pattern were observed, as shown in Fig.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…The increased time resulted in diF-TES-ADT crystals with larger grain size. This is in accordance with the work of Qiu et al, which reports similar concentration effects in P3HT/PMMA blends [9]. When the solution concentration was increased further (30 mg/ml), spherulites with a Maltese cross pattern were observed, as shown in Fig.…”
Section: Resultssupporting
confidence: 93%
“…Because charge transport occurs at the dielectric/semiconductor interface laterally, the conducting pathway from the source to drain electrode should be well-defined. Therefore, inducing vertical phase separation is an effective method for obtaining high mobility in OFETs [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21]. For example, it has been demonstrated that a phase-separated structure comprising an insulating polymer top layer and an organic semiconductor bottom layer-poly(methyl methacrylate) (PMM A)-top/poly(3-hexylthiophene) (P3HT)-bottom-increases environmental stability in bottom-gate/bottom-contact OFETs [6].…”
Section: Introductionmentioning
confidence: 99%
“…Low voltage driven OFETs have been successfully fabricated because a phase-separated thin PMMA layer can work as a gate dielectric (Figure 3b). Wang et al, examined the effect of film processing conditions (i.e., solution concentration) on the morphology of the phase-separated interface between P3HT and PMMA [30]. A higher solution concentration tended to decrease roughness of the phase-separated interface.…”
Section: Vertical Phase-separationmentioning
confidence: 99%
“…[23,24] This pioneering work focused on the methodology of this approach rather than incorporating these patterned layers in electronic devices. Morphology control by surface directed phase separation was explored in organic light emitting diodes [ 25 , 26 , 27 ] , photovoltaics [28] and thin film transistors [29,30] . Next, we show that this bottom-up approach also works for ferroelectric-semiconductor blends.…”
Section: Blend Layer Processing On Substrates With Patterned Samsmentioning
confidence: 99%